1994
DOI: 10.1002/cjce.5450720320
|View full text |Cite
|
Sign up to set email alerts
|

Use of mixed surfactants to improve the transient interfacial tension behaviour of heavy oil/alkaline systems

Abstract: The objective of this study was to identify suitable combinations of additives to aqueous alkaline formulations for the potential recovery of Saskatchewan heavy crude oil. A previously developed strategy was applied to screen various additive combinations consisting of three commercial petroleum sulfonate surfactants and two commercial lignosulfonate surfactants. The selection of the additives was based on a large number of physical and interfacial property measurements in conjunction with phase stability test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…This behaviour could be due to the role of micelles on the oil transfer. Similar observations were made by Chiwetelu et al [17] for mixed surfactant enhanced alkaline/heavy crude oil. However in their case, the initial IFT values were considerably higher than those exhibited by the surfactant free system.…”
Section: Resultssupporting
confidence: 89%
“…This behaviour could be due to the role of micelles on the oil transfer. Similar observations were made by Chiwetelu et al [17] for mixed surfactant enhanced alkaline/heavy crude oil. However in their case, the initial IFT values were considerably higher than those exhibited by the surfactant free system.…”
Section: Resultssupporting
confidence: 89%
“…Rudin et al (21) suggested that the dominant mechanism by which added surfactant aids in the reduction of IFT was the formation of mixed micelles with the ionized acid. Chiwetelu et al (22) reported that the addition of mixtures of surfactants to NaOH solutions successfully reversed the undesirable trend of increasing IFT with time. Chatterjee et al (23) found that there existed an optimal pH which produces ultralow IFT in alkali/acidic oil systems.…”
Section: Introductionmentioning
confidence: 97%
“…Surfactant mixtures have been used in enhanced oil recovery processes to produce ultra-low interfacial tension (1,2) or curb undesired behavior such as adsorption (3).…”
Section: Introductionmentioning
confidence: 99%